2014
DOI: 10.1161/strokeaha.113.004629
|View full text |Cite
|
Sign up to set email alerts
|

Localized Retinal Nerve Fiber Layer Defects and Stroke

Abstract: Background and Purpose-Because the blood circulation system of retina and brain are closely related to each other, we examined whether stroke is associated with localized retinal nerve fiber layer defects (RNFLDs). Methods-Patients with acute ischemic stroke as part of a hospital-based study group were compared with the participants of the population-based group Beijing Eye Study. The retina was imaged by spectral-domain optical coherence tomography for the detection of localized RNFLDs. Results-The study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 28 publications
7
43
2
1
Order By: Relevance
“…24 In a hospital-based study, localized RNFLDs were significantly associated with acute or preceding cerebral stroke after adjusting for arterial blood pressure and other factors associated with stroke or localized RNFLDs. 25 These preceding cross-sectional hospital-based studies, the experimental monkey study, and the present longitudinal populationbased investigations agree on the association between localized RNFLDs and arterial hypertension and cerebral stroke. It suggests that localized RNFLDs should be searched for in any patients with arterial hypertension and/or at risk for stroke.…”
Section: Discussionsupporting
confidence: 86%
“…24 In a hospital-based study, localized RNFLDs were significantly associated with acute or preceding cerebral stroke after adjusting for arterial blood pressure and other factors associated with stroke or localized RNFLDs. 25 These preceding cross-sectional hospital-based studies, the experimental monkey study, and the present longitudinal populationbased investigations agree on the association between localized RNFLDs and arterial hypertension and cerebral stroke. It suggests that localized RNFLDs should be searched for in any patients with arterial hypertension and/or at risk for stroke.…”
Section: Discussionsupporting
confidence: 86%
“…Injuries in neurovascular coupling mechanism, which is important in the brain homeostasis, are also present in pathologic conditions such as stroke, subarachnoid hemorrhage, and dementias. 37 Recent surveys have found that localized RNFL defects are also associated with neurodegenerative diseases such as stroke 38 or small vessel disease 39 ; they are also associated with arterial hypertension. 40 In this regard, RNFL defect in diabetes seems to be one manifestation other than DR, which could be used as one of the surrogate markers of impaired neurovascular coupling in neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…Focal retinal nerve fiber layer defects, thought to represent prior ischemic insults to the retina, were more common in both cross sectional and cohort stroke groups versus a cohort derived control group. (46) This may be a surrogate marker for prior RAO, though guidelines do not currently recommend secondary stroke prevention on this basis.…”
Section: Relationship Between Chronic Retinal Microvascular Disease Amentioning
confidence: 99%